2007
DOI: 10.1074/jbc.m703278200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role for the Liver X Nuclear Receptor in the Suppression of Lung Inflammatory Responses

Abstract: The liver X receptors (LXR␣/␤) are part of the nuclear receptor family and are believed to regulate cholesterol and lipid homeostasis. It has also been suggested that LXR agonists possess anti-inflammatory properties. The aim of this work was to determine the effect of LXR agonists on the innate immune response in human primary lung macrophages and a pre-clinical rodent model of lung inflammation. Before profiling the impact of the agonist, we established that both the human macrophages and the rodent lungs ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 25 publications
(37 reference statements)
2
44
0
1
Order By: Relevance
“…While statins do exert some effects on leukocyte function by depleting cellular cholesterol (84), other effects stem from depletion of cellular isoprenoids and consequent inhibition of cellular protein prenylation (80). Systemic treatment of rodents with synthetic agonists of Liver X Receptor (LXR), a nuclear receptor that promotes cellular cholesterol efflux and reverse cholesterol transport, has also been shown to reduce PMN recruitment into the airspace induced by LPS and Gram-negative bacteria (85,86). A potential untoward consequence of reduced PMN recruitment to the lung through cholesterol targeting is impaired antibacterial host defense, as both statins and LXR agonists also reduce clearance of bacteria deposited in the rodent lung (80,86).…”
Section: Emerging Roles For Cholesterol In Pmn Recruitment To the Lungmentioning
confidence: 99%
“…While statins do exert some effects on leukocyte function by depleting cellular cholesterol (84), other effects stem from depletion of cellular isoprenoids and consequent inhibition of cellular protein prenylation (80). Systemic treatment of rodents with synthetic agonists of Liver X Receptor (LXR), a nuclear receptor that promotes cellular cholesterol efflux and reverse cholesterol transport, has also been shown to reduce PMN recruitment into the airspace induced by LPS and Gram-negative bacteria (85,86). A potential untoward consequence of reduced PMN recruitment to the lung through cholesterol targeting is impaired antibacterial host defense, as both statins and LXR agonists also reduce clearance of bacteria deposited in the rodent lung (80,86).…”
Section: Emerging Roles For Cholesterol In Pmn Recruitment To the Lungmentioning
confidence: 99%
“…It has been confirmed that LXRs strongly exert anti-inflammatory effects in the mouse models of inflammation, such as collagen-induced arthritis, 8) atherosclerosis, 9) and LPSinduced hepatic 10) or lung injury. 11,12) LXR agonist T0901317 (TO) has been indicted to suppress inflammatory responses in the lung of rats with acute lung injury induced by LPS through the inhibition of NF-κB activation. 12) Similarly, LXRs seem to protect cardiac function against myocardial ischemia/reperfusion injury by inhibition of inflammation.…”
Section: Liver X Receptor Activation Protects Against Inflammation Anmentioning
confidence: 99%
“…These findings provide a potential pathway to target inflammatory airway diseases including asthma. [84] However, conflicting results have been shown with respect to the effect of LXR activation on the growth of airway smooth muscle cells. [83,85] Using an in vivo model of allergic inflammation, LXR activation caused an increase in airway reactivity due to increased smooth muscle thickness.…”
Section: Vi) Lung and Kidneymentioning
confidence: 99%